Anticancer Activity Driven by Drug Linker Modification in a Polyglutamic Acid‐Based Combination‐Drug Conjugate. (16th April 2018) - Arroyo‐Crespo, Juan J.; Deladriere, Coralie; Nebot, Vicent J.; Charbonnier, David; Masiá, Esther; Paul, Alison; James, Craig; Armiñán, Ana; Vicent, María J.
Abstract: Combination nanotherapies for the treatment of breast cancer permits synergistic drug targeting of multiple pathways. However, poor carrier degradability, poor synergism of the combined drugs, low drug release regulation, and a lack of control on final macromolecule solution conformation (which drives the biological fate) limit the application of this strategy. The present study describes the development of a family of drug delivery systems composed of chemotherapeutic (doxorubicin) and endocrine therapy (aromatase inhibitor aminoglutethimide) agents conjugated to a biodegradable poly‐l ‐glutamic acid backbone via various linking moieties. Data from in vitro cytotoxicity and drug release assessments and animal model validation select a conjugate family member with optimal biological performance. Exhaustive physicochemical characterization in relevant media (including the study of secondary structure, size measurements, and detailed small‐angle neutron scattering analysis) correlates biological data with the intrinsic supramolecular characteristics of the conjugate. Overall, this study demonstrates how a small flexible Gly linker can modify the spatial conformation of the entire polymer–drug conjugate, promote the synergistic release of both drugs, and significantly improve biological activity. These findings highlight the need for a deeper understanding of polymer–drug conjugates at supramolecular level to allow the design of more effective polymer–drug conjugates. Abstract : A complex interplay of physical factors drives the interaction between nanomaterials and the biointerface. A panel of physicochemical descriptors allows a structure–anticancer activity relationship to be established for a wide family of biodegradable polyglutamate–drug conjugates, bearing synergistic loadings of chemotherapeutic and endocrine agents, highlighting the crucial role of a small glycine drug linker.